Exploring the effect of bacterial endophytes on mitigating salinity stress in tomato - singaram, ambika; S. LAKSHMI (The Indian Journal of Agricultural Sciences, 2026)
One of the most significant factors influencing global crop production is salt stress. Plants adapt to salinity stress using a variety of physiological, morphological, and molecular mechanisms. However, several mitigation strategies are being used to deal with the severe effects of salt stress. Microbial agents, notably bacterial endophytes, have been shown to be salinity tolerance, enhancing plant survival under saline stress. The present study was carried out during 2023–2024 and 2024–2025 at Tamil Nadu Agricultural University, Coimbatore. Tomato cv. PKM 1 seed were bioprimed with Bacillus firmis (1:1), Bacillus paralicheniformis (undiluted broth), Bacillus amyloliquefaciens (undiluted broth), Bacillus velezensis (1:1) along with water (hydro priming) for 12 h. Seeds which were primed with endophytes and untreated control seeds were raised in pro tray and transplanted in the pot after 25 days. The pot was filled with soil and various salinity levels (0 mM, 25 mM, 50 mM and 75 mM NaCl) were created. Best treatments resulted in pot culture along with control viz., seeds bioprimed with Bacillus paralicheniformis suspension, Bacillus firmis suspension), were raised in hydrophonic method and root exudates were collected and analysed through GCMS. The result revealed that tomato seeds bioprimed with Bacillus paralicheniformis and Bacillus firmus recorded the higher physiological and growth parameters under different salinity conditions. Seeds bioprimed with undiluted suspension of Bacillus paralicheniformis recorded more biomolecules which may be responsible for phytohormone production, stimulation of antioxidant enzyme activity and resulted in improved vigour and germination of tomato seedlings under salinity stress conditions. The results confirmed that tomato seeds can be bioprimed with Bacillus paralicheniformis to overcome the salinity stress.